Optimisation of Microstrip Antenna - El Hamchary, H. (Radioengineering Society, 1996)
When choosing the most appropriate microstrip antenna configuration for particular applications, the kind of excitation of the radiating element is an essential factor that requires careful considerations. For controlling the distribution of energy of the linear or planar array of elements and for coupling energy to the individual elements, a wide variety of feed mechanisms are available. In this paper, the coaxial antenna feeding is assumed and the best (optimised) feeding is found. Then, antenna characteristics such as radiation pattern, return loss, input impedance, and VSWR are obtained.
Keywords: microstrip antenna; VSWR